Intranasal immunization with curdlan induce Th17 responses and enhance protection against enterovirus 71 - Yi, Eun Je; Kim, Young In; Song, Jae Hyoung; Ko, Hyun Jeong; Chang, Sun Young (Vaccine, 2023)
Mucosal surfaces are in contact with the external environment and protect the body from infection by various microbes. To prevent infectious diseases at the first line of defense, the establishment of pathogen-specific mucosal immunity by mucosal vaccine delivery is needed. Curdlan, a 1,3-β-glucan has a strong immunostimulatory effect when delivered as a vaccine adjuvant. Here, we investigated whether intranasal administration of curdlan and antigen (Ag) could induce sufficient mucosal immune responses and protect against viral infections. Intranasal co-administration of curdlan and OVA increased OVA-specific IgG and IgA Abs in both serum and mucosal secretions. In addition, intranasal co-administration of curdlan and OVA induced the differentiation of OVA-specific Th1/Th17 cells in the draining lymph nodes. To investigate the protective immunity of curdlan against viral infection, intranasal co-administration of curdlan with recombinant VP1 of EV71 C4a was administered and showed enhanced protection against enterovirus 71 in a passive serum transfer model using neonatal hSCARB2 mice, although intranasal administration of VP1 plus curdlan increased VP1-specific helper T cells responses but not mucosal IgA. Next, Mongolian gerbils were intranasally immunized with curdlan plus VP1, and they had effective protection against EV71 C4a infection, while decreasing viral infection and tissue damage by inducing Th17 responses. These results indicated that intranasal curdlan with Ag improved Ag-specific protective immunity by enhancing mucosal IgA and Th17 against viral infection. Our results suggest that curdlan is an advantageous candidate as a mucosal adjuvant and delivery vehicle for the development of mucosal vaccines.
Keywords: Adjuvants, Immunologic; Administration, Intranasal; Animals; Antigens; Enterovirus; Enterovirus A, Human; Immunity, Mucosal; Immunization; Immunoglobulin A; Mice; Mice, Inbred BALB C; Th17 Cells; Adjuvant; Curdlan; Enterovirus 71; Intranasal delivery; Mucosal vaccine